Assessment of self-medication among dental students in Pune city, Maharashtra: A cross-sectional survey - Dheeraj Deepak Kalra; Prajna V Kini; Rinku D Kalra; Vinod R Jathanna (Wolters Kluwer Medknow Publications, 2015)
Introduction: In the recent years, there has been an increasing trend in self-medication with nonprescription (over-the-counter) drugs available in pharmacies and retail outlets. There are both advantages and disadvantages of self-medication. Data pertaining to the prevalence of self-medication among dental students in India is scarce. Aim: To determine the level of self-medication among the dental students. Materials and Methods: Descriptive cross-sectional questionnaire study was conducted on 548 dental students from I BDS to IV BDS, interns, and postgraduate students, in classroom setting in census type, hand delivery of questionnaires was done. Out of that, 494 questionnaires were returned duly filled and analyzed. Data analysis were done using SPSS software (v 22.0, IBM). Results: A total of 40.9% of respondents indulged in self-medication. Both male and female dental students equally had a habit of taking medicines on their own. The most common drugs used for self-medication were antipyretics (46.56%), followed by analgesics (40.08%), and cough syrups (18.02%). Cold (19.43%) was the major indication for self-medication, followed by (18.02%) a cough, and (16.19%) was a fever. Most common reason not to see a doctor was that there is no need to see a doctor because of a simple disease (31.58%) followed by the need for a quick relief (20.45%). The predominant guiding sources of information for students was media (magazines and internet) (38.06%) and books (39.88%). Conclusion: The majority of students indulged in the practice of self-medication though they had poor knowledge of the benefits and risks.